2015
DOI: 10.1891/1946-6560.6.3.298
|View full text |Cite
|
Sign up to set email alerts
|

The Price of Distrust: Trust, Anxious Attachment, Jealousy, and Partner Abuse

Abstract: Trust is essential to the development of healthy, secure, and satisfying relationships (Simpson, 2007a). Attachment styles provide a theoretical framework for understanding how individuals respond to partner behaviors that either confirm or violate trust (Hazan & Shaver, 1994). The current research aimed to identify how trust and attachment anxiety might interact to predict different types of jealousy and physical and psychological abuse. We expected that when experiencing lower levels of trust, anxiously atta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 91 publications
4
44
2
1
Order By: Relevance
“…Losing a partner may demotivate quitters from successfully maintaining smoking cessation 16 17 33. Additionally, being separated, divorced or widowed might drive a general feeling of insecurity and anxiety,42 43 which could explain the higher rates of relapse found among these subgroups in our analysis.…”
Section: Discussionmentioning
confidence: 90%
“…Losing a partner may demotivate quitters from successfully maintaining smoking cessation 16 17 33. Additionally, being separated, divorced or widowed might drive a general feeling of insecurity and anxiety,42 43 which could explain the higher rates of relapse found among these subgroups in our analysis.…”
Section: Discussionmentioning
confidence: 90%
“…Attachment anxiety is a hyperactivating affect regulation style featuring rumination about relationships, heightened negative affect, and negative self-views [ 65 ]. Attachment anxiety is associated with low trust [ 66 ] and poor emotion regulation [ 67 ]. Attachment avoidance is associated with distancing strategies, which can manifest as low empathy [ 68 ] and relationship destructive behaviours [ 69 ].…”
Section: Studymentioning
confidence: 99%
“…Previous research has shown that economic inequality leads to a sense of injustice and destroys interpersonal distrust (Bernstein & Crosby, 1980;Smith et al, 2012;Uslaner, 2013). On the other hand, Giddens' duality of structure can be used as theoretical support: distrust as a psychological inducement can affect the individual's subjective choice and produce extreme anxiety and anger, which eventually leads to violent behaviour; the rebellion itself then becomes an influencing factor and alters feelings of trust and behavioural choices, creating a vicious cycle of distrust and violence (Giddens, 1998;Rodriguez, Dibello, Øverup, & Neighbors, 2015). Moreover, Schul and Peri (2015) also report that trust exerted an impact on individuals' behavioural decisions.…”
Section: Discussionmentioning
confidence: 99%